SISTEM INFORMASI GEOGRAFIS PENCARIAN TENGKULAK HASIL TANI DI KECAMATAN BRINGIN - Ardella Sanfirsty; Nicky Yuda Apriyanto; Cahyo Darujati (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2022)
Kecamatan Bringin is one of the areas in Ngawi Regency where the mass of people are agriculturalists. In selling their agricultural products, farmers will sell to middlemen, namely agents who buy the product from the first owner. In seeking information about the middleman, agriculturalists lean on information by word of mouth. Many farmers and rural villagers are already actively using smartphones. According to the statement, this research held to build a geographic information system for finding the middleman. Aim to make it easier for people to find places to sell their products. This geographic information system was designed using the waterfall method with the Unified Modeling Language (UML) tool in the system design. This system is a web-based application using PHP with the CodeIgniter 4 framework and MySQL. System data is accumulated by observing and interviewing the middleman. Data collection was input into the system to make information of middleman obtained. That information can be accessed by the user easily. The information obtained is in the addresses, telephone numbers of the middleman, the products purchased, and the route to the location of the middleman. Validate the feasibility of the application by testing using BlackBox testing. The results accepted that the application procedure worked properly according to its functionality.